Optimality of a monetary union : New evidence from exchange rate misalignments in West Africa - (:unkn) unknown (My University, 2012)
This paper aims to study the optimality of a monetary union in West Africa by using a new methodology based on the analysis of convergence and co-movements between exchange rate misalignments. Two main advantages characterize this original framework. First, it brings together the information related to several optimum currency area criteria— such as price convergence, terms of trade shocks, and trade and fiscal policies—going further than previous studies which are mainly based on only one criterion at a given time. Second, our study detects potential competitiveness differentials which play a key role in the debate on the optimality or not of a monetary union, as evidenced by the recent crisis in the Euro area. Relying on recent panel cointegration techniques and cluster analysis, our results show that the WAEMU area has a core composed by Burkina Faso, Mali, Niger and Senegal which can be joined by Ghana, Sierra Leone and, to a lesser extent, Gambia, and that Ghana and Senegal appear to be the best reference countries for the creation of the whole West Africa monetary union.
Keywords: African Research